STUDY OF PHOTOCATALYTIC EFFECT USING ZNO NANOROD MATERIAL THROUGH THE DEGRADATION TEST OF METHYLENE BLUE DYE - Fiwendi
Photocatalysis is a practical and efficient method for treating waste dyes. The photocatalytic mechanism utilizes the help of UV rays and the chemical reaction of photocatalyst material to degrade the waste of dyes into substances that are not harmful to living things and ecosystems. This research focuses on ZnO nanorod as a photocalist material doped with Titanium (Ti) 14% to optimize its performance. ZnO nanorod growth method used is the hydrothermal method. The dye sample used in this study was Methylene Blue (C16H18ClN3S). The morphological and structural properties of ZnO nanorods were characterized by Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD). The photodegradation quality of Methylene Blue was determined through UV-Vis spectroscopy with UV exposure times successively 0, 5, 10, 15, 20, 25 and 30 minutes. SEM characterization results showed that the growth of ZnO nanorod has a diameter of about 120 nm. The XRD characterization results obtained 3 pieces of the dominant peak of the ZnO nanorod diffraction pattern. Whereas the results of the photocatalysis test using UV-Vis spectroscopy showed the absorbance of the Methylene Blue dye decreased within 30 minutes on ZnO nanorods. This indicates that Methylene Blue (C16H18ClN3S) breaks down into C16H18N3S molecules.